If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(7x + 5) = 182 Reorder the terms: 7(5 + 7x) = 182 (5 * 7 + 7x * 7) = 182 (35 + 49x) = 182 Solving 35 + 49x = 182 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + 49x = 182 + -35 Combine like terms: 35 + -35 = 0 0 + 49x = 182 + -35 49x = 182 + -35 Combine like terms: 182 + -35 = 147 49x = 147 Divide each side by '49'. x = 3 Simplifying x = 3
| 7x^3/16-9x^3/16 | | -9+3+w=35 | | 0.2x+0.3=1.4 | | 2+2y=-4 | | 7x^2-4=21x-4 | | 3x+9x=54 | | 21X^2+14X=0 | | -5+2=2x-8-x | | -8=-4(x+4) | | C=5000+6Q | | 21x^2+14=0 | | (3y-12)+5x=(x+32)+(2y+5) | | 3x+18=4x+12 | | u-10=v | | 18x+15-17x=-9 | | 3w^2-w-24=0 | | (4p^9q/r^5)^2 | | 4z^2-z-39=0 | | 5-2y=6 | | y+2=-3x | | 1/3t-t=15 | | 6-6x-3=29+3x-13 | | 1/3-x-x=15 | | -4-(-34)+33+40-(-12)= | | -0.5h-7=-11 | | 3x-15=7x-75 | | -1/2c-7=-11 | | g-0.25=.625 | | 58.5=3.5x-2 | | 5(x-3)=7x-2(x-1) | | 28d+20=50 | | -.40+14= |